Academic Library System:Fourth Plan Period - Ranganathan, S. R. (Journal of Information and Knowledge, 2000)
Forms the introduction to the remaining papers in this issue. Gives the financial requirements of the academic library system of India, as 2,336 million rupees for all the five years of the Fourth Plan Period. Traces the slow changeover from text-book-centred, mass-talk method of teaching into library-centred, individual and group guidance method. Establishes standards for university, college, secondary, and elementary education library systems.